Fatores relacionados às perdas dentárias em adultos e idosos em um município de médio porte no nordeste do Brasil - Maia, Fabiana Barros Marinho (2015)
Introduction: In the adult stage of life occurs the greatest number of tooth loss, which causes an increasing number of edentulous. Objective: This study examined factors related to tooth loss in adults and elderly of a medium-sized municipality in northeastern Brazil. Methodology: This study was a study of observational, cross-sectional ecological and done through home visits using the codes and criteria of SBBrasil (2010). 212 adults of both sexes were examined. The outcome of the study was tooth loss, obtained from its occurrence ("missing teeth" component of DMFT index) and classified in two models: a) distribution of tooth loss by the median of 24 teeth and b) using up to 12 missing teeth including the foregoing. We used the chi-square and Fisher exact test, significant with p <0.05, considering the multiple logistic regression model. Results: It was observed that the mean value of DMFT was 27.0, and tooth loss the most significant component, averaging 23.05 with no significant difference between the sexes (p = 0.665). About 83% of the sample studied up to 8 years and 52.9% received one minimum wage or more, showing no relationship to tooth loss. The time of the last visit to the dentist greater than 1 year was 72.6% (p = 0.00) for both the median loss of teeth 24 and the tooth 12 for; those who presented the review / prevention as a reason for the last consultation were respectively 89.59% and 71.87% lower chance of losing teeth; towards those who have lost up to 12 teeth and who rated the quality of life in oral health with more of an impact obtained p = 0.05 chance presenting 2.25 times more tooth loss compared with those who rated no impact, and variables presenting relation to tooth loss. Conclusion: In both the variables and time of last visit reason models studied presented themselves as risk factors and similar protection, regardless of the number of missing teeth.